Long-term trends in the burden of inflammatory bowel disease in China over three decades: A joinpoint regression and age-period-cohort analysis based on GBD 2019 - Zhang, Yang; Liu, Jiali; Han, Xiao; Jiang, Hui; Zhang, Liming; Hu, Juncong; Shi, Lei; Li, Junxiang (Frontiers in Public Health, 2022)
Background: To study the corresponding strategies to control inflammatory bowel disease (IBD), a comprehensive assessment of the disease burden is required. Herein, we present long-term trends in the burden of IBD in China over the last three decades, as well as its epidemiological features. Methods: We characterized the burden of IBD in China using the GBD 2019 methods and results, based on prevalence, incidence, mortality, years lost (YLLs), years lived with disability (YLDs), and disability-adjusted life years (DALYs) estimated using the DisMod-MR 2-1. We also used joinpoint and age-period-cohort (apc) analysis methods to interpret IBD epidemiological characteristics and compare them to global prevalence trends. Results: The age-standardized incidence and mortality rates in both sexes changed from 1.47 (95% CI: 1.24,1.74) to 3.01 (95% CI: 2.59,3.50) and from 0.86 (95% CI: 0.59,1.16) to 0.30 (95% CI: 0.24,0.35) per 100,000 people in China from 1990 to 2019. The age-standardized DALY rate in China decreased from 24.47 (95% CI: 17.88,30.19) per 100,000 people in 1990 to 13.10 (95% CI: 10.29,16.31) per 100,000 people in 2019. The average annual percentage change (AAPC) in age-standardized incidence, prevalence, and mortality rates for IBD in China were 2.51 (95% CI: 2.44,2.57), 2.53 (95% CI: 2.41,2.66), and -3.62 (95% CI: -3.85,-3.39). The effects of age, period, and cohort on incidence and mortality rates differed. Conclusions: The increasing age-standardized prevalence rates are contributed to by the reduction in age-standardized mortality rates and DALYs, compounded by the rise in the age-standardized incidence rates between 1990 and 2019 in China. The burden of IBD in China will be a major public health challenge, given the country’s large population base and aging population.